Cold-adapted yeasts for hydrocarbon degradation: bioremediation insights from extreme environments - Bryan Guerra; Gianmarco Mugnai; Ciro Sannino; Benedetta Turchetti; Fabiana Canini; Pietro Buzzini; Laura Zucconi; Solveig Tosi (International Biodeterioration & Biodegradation, 2026)

Cold-based glaciers and underlying permafrost: A possible new habitat for fungi - Gianmarco Mugnai; Ciro Sannino; Luigimaria Borruso; Daniele Andreani; Dario Battistel; Benedetta Turchetti; Pietro Buzzini; Mauro Guglielmin (Applied Soil Ecology, 2025)

Implications of nurse species in mixed forest plantations management on soil fungal community diversity - Tiziana Danise; Olga De Castro; Claudio Zaccone; Georg Guggenberger; Cristina Menta; Michele Innangi; Daniele De Luca; Emanuela Di Iorio; Benedetta Turchetti; Antonietta Fioretto (Applied Soil Ecology, 2025)

Clinical genetic services in the Emilia-Romagna region, Italy: current activity and open issues: a mixed-method study - Lea Godino; Enrico Ambrosini; Valeria Barili; Claudio Graziano; Livia Garavelli; Olga Calabrese; Marcella Neri; Luca Sangiorgi; Benedetta Bertonazzi; Giovanni Innella; Daniela Turchetti; Antonio Percesepe (Journal of Community Genetics, 2025)
In 2002, in the Emilia-Romagna region of Italy, a comprehensive strategic plan was developed with the aim of improving the integration and efficiency of the genetic services. Two decades later, this report aims to explore the current functioning of the regional network, with special focus on clinical genetics in the evolving scenarios. To this aim, we analyzed the activity data of the medical genetics services in the region, to identify and possibly improve currently open issues. This is a mixed-method study, analyzing quantitatively and qualitatively the activities of seven medical genetics services in Emilia-Romagna region. Quantitative analysis considered the number of consultations and the composition of the staff in the year 2021. Qualitative analysis examined a focus group of directors of the services through reflexive thematic analysis. A total of 14,925 counseling sessions have been delivered by the medical genetics services, staffed with 22.4 full-time equivalent clinical geneticists. A physician performed an average of 14.5 consultations per week and approximately 1166 h of patient care per year. The clinical geneticists/inhabitants ratio was 0.54 per 100,000 inhabitants, and it is estimated that one every 278 inhabitants, on average, underwent a genetic counseling session in 2021. Qualitative analysis highlighted issues concerning patients’ access to service, general organization and staff composition. In order to meet the growing demand for genetic counseling services, expansion of the workforce and adjustment of current practice models are required to increase the access to genetic services and the application of test results to clinical management.

Selective response of soil bacterial and fungal taxa to biodegradable polymers - Alessandro Bernetti; Sofia Barili; Ciro Sannino; Gianmarco Mugnai; Luigimaria Borruso; Irina Pinchuk; Daniela Pezzolla; Benedetta Turchetti; Giovanni Gigliotti; Pietro Buzzini (Environmental Research, 2025)

Microplastics in the diet of Hermetia illucens: Implications for development and midgut bacterial and fungal microbiota - Silvana Piersanti; Manuela Rebora; Benedetta Turchetti; Gianandrea Salerno; Mario Ruscetta; Laura Zucconi; Federica D’Alò; Pietro Buzzini; Ciro Sannino (Waste Management, 2024)

The hidden network of biocrust successional stages in the High Arctic: Revealing abiotic and biotic factors shaping microbial and metazoan communities - Gianmarco Mugnai; Irina Pinchuk; Luigimaria Borruso; Raphael Tiziani; Ciro Sannino; Fabiana Canini; Benedetta Turchetti; Tanja Mimmo; Laura Zucconi; Pietro Buzzini (Science of The Total Environment, 2024)

Exploring different methodological approaches to unlock paleobiodiversity in peat profiles using ancient DNA - Ilaria Fracasso; Claudio Zaccone; Nikolay Oskolkov; Luca Da Ros; Anna Dinella; Luca Belelli Marchesini; Pietro Buzzini; Ciro Sannino; Benedetta Turchetti; Stefano Cesco; Gael Le Roux; Giustino Tonon; et al. (Science of The Total Environment, 2024)

Species and temperature-dependent fermentative aptitudes of Mrakia genus for innovative brewing - Benedetta Turchetti; Giovanni De Francesco; Gianmarco Mugnai; Valeria Sileoni; Vincenzo Alfeo; Pietro Buzzini; Andrey Yurkov; Ombretta Marconi (Food Research International, 2023)

Impact of PVC microplastics on soil chemical and microbiological parameters - Sofia Barili; Alessandro Bernetti; Ciro Sannino; Nicolò Montegiove; Eleonora Calzoni; Alessio Cesaretti; Irina Pinchuk; Daniela Pezzolla; Benedetta Turchetti; Pietro Buzzini; Carla Emiliani; Giovanni Gigliotti (Environmental Research, 2023)

Fungal communities in European alpine soils are not affected by short‐term in situ simulated warming than bacterial communities - Ciro Sannino; Nicoletta Cannone; Federica D'Alò; Andrea Franzetti; Isabella Gandolfi; Francesca Pittino; Benedetta Turchetti; Ambra Mezzasoma; Laura Zucconi; Pietro Buzzini; Mauro Guglielmin; Silvano Onofri (Environmental Microbiology, 2022)
The impact of global warming on biological communities colonizing European alpine ecosystems was recently studied. Hexagonal open top chambers (OTCs) were used for simulating a short‐term in situ warming (estimated around 1°C) in some alpine soils to predict the impact of ongoing climate change on resident microbial communities. Total microbial DNA was extracted from soils collected either inside or outside the OTCs over 3 years of study. Bacterial and fungal rRNA copies were quantified by qPCR. Metabarcoding sequencing of taxonomy target genes was performed (Illumina MiSeq) and processed by bioinformatic tools. Alpha‐ and beta‐diversity were used to evaluate the structure of bacterial and fungal communities. qPCR suggests that, although fluctuations have been observed between soils collected either inside and outside the OTCs, the simulated warming induced a significant ( p p p

Intra‐ and inter‐cores fungal diversity suggests interconnection of different habitats in an Antarctic frozen lake (Boulder Clay, Northern Victoria Land) - Ciro Sannino; Luigimaria Borruso; Ambra Mezzasoma; Dario Battistel; Laura Zucconi; Laura Selbmann; Maurizio Azzaro; Silvano Onofri; Benedetta Turchetti; Pietro Buzzini; Mauro Guglielmin (Environmental Microbiology, 2020)
Summary A perennially frozen lake at Boulder Clay site (Victoria Land, Antarctica), characterized by the presence of frost mounds, have been selected as an in situ model for ecological studies. Different samples of permafrost, glacier ice and brines have been studied as a unique habitat system. An additional sample of brines (collected in another frozen lake close to the previous one) was also considered. Alpha‐ and beta‐diversity of fungal communities showed both intra‐ and inter‐cores significant ( p The predominance of positive significant ( p p

Characterization of basidiomycetous yeasts in hypersaline soils of the Urmia Lake National Park, Iran - Lachin Mokhtarnejad; Mahdi Arzanlou; Asadollah Babai-Ahari; Simone Di Mauro; Andrea Onofri; Pietro Buzzini; Benedetta Turchetti (Extremophiles, 2016)

Seasonal and altitudinal changes of culturable bacterial and yeast diversity in Alpine forest soils - Luís França; Ciro Sannino; Benedetta Turchetti; Pietro Buzzini; Rosa Margesin (Extremophiles, 2016)

Application of anhydrobiosis and dehydration of yeasts for non-conventional biotechnological goals - Alexander Rapoport; Benedetta Turchetti; Pietro Buzzini (World Journal of Microbiology and Biotechnology, 2016)

A population genomics insight into the Mediterranean origins of wine yeast domestication - Pedro Almeida; Raquel Barbosa; Polona Zalar; Yumi Imanishi; Kiminori Shimizu; Benedetta Turchetti; Jean‐Luc Legras; Marta Serra; Sylvie Dequin; Arnaud Couloux; Julie Guy; Douda Bensasson; et al. (Molecular Ecology, 2015)
The domestication of the wine yeast Saccharomyces cerevisiae is thought to be contemporary with the development and expansion of viticulture along the Mediterranean basin. Until now, the unavailability of wild lineages prevented the identification of the closest wild relatives of wine yeasts. Here, we enlarge the collection of natural lineages and employ whole‐genome data of oak‐associated wild isolates to study a balanced number of anthropic and natural S. cerevisiae strains. We identified industrial variants and new geographically delimited populations, including a novel Mediterranean oak population. This population is the closest relative of the wine lineage as shown by a weak population structure and further supported by genomewide population analyses. A coalescent model considering partial isolation with asymmetrical migration, mostly from the wild group into the Wine group, and population growth, was found to be best supported by the data. Importantly, divergence time estimates between the two populations agree with historical evidence for winemaking. We show that three horizontally transmitted regions, previously described to contain genes relevant to wine fermentation, are present in the Wine group but not in the Mediterranean oak group. This represents a major discontinuity between the two populations and is likely to denote a domestication fingerprint in wine yeasts. Taken together, these results indicate that Mediterranean oaks harbour the wild genetic stock of domesticated wine yeasts.

A novel killer protein from Pichia kluyveri isolated from an Algerian soil: purification and characterization of its in vitro activity against food and beverage spoilage yeasts - Fatima-Zohra Kenza Labbani; Benedetta Turchetti; Leila Bennamoun; Scheherazad Dakhmouche; Rita Roberti; Lanfranco Corazzi; Zahia Meraihi; Pietro Buzzini (Antonie van Leeuwenhoek, 2015)

Cryptococcus vaughanmartiniae sp. nov. and Cryptococcus onofrii sp. nov.: two new species isolated from worldwide cold environments - Benedetta Turchetti; Laura Selbmann; Robert A. Blanchette; Simone Di Mauro; Elisabetta Marchegiani; Laura Zucconi; Brett E. Arenz; Pietro Buzzini (Extremophiles, 2015)

Description of Taphrina antarctica f.a. sp. nov., a new anamorphic ascomycetous yeast species associated with Antarctic endolithic microbial communities and transfer of four Lalaria species in the genus Taphrina - Laura Selbmann; Benedetta Turchetti; Andrey Yurkov; Clarissa Cecchini; Laura Zucconi; Daniela Isola; Pietro Buzzini; Silvano Onofri (Extremophiles, 2014)

Adaptation of fungi, including yeasts, to cold environments - Oriana Maggi; Solveig Tosi; Maria Angelova; Elisa Lagostina; Anna Adele Fabbri; Lorenzo Pecoraro; Elisa Altobelli; Anna Maria Picco; Elena Savino; Eva Branda; Benedetta Turchetti; Mirca Zotti; et al. (Plant Biosystems, 2013)

Psychrophilic yeasts from Antarctica and European glaciers: description of Glaciozyma gen. nov., Glaciozyma martinii sp. nov. and Glaciozyma watsonii sp. nov. - Benedetta Turchetti; Skye R. Thomas Hall; Laurie B. Connell; Eva Branda; Pietro Buzzini; Bart Theelen; Wally H. Müller; Teun Boekhout (Extremophiles, 2011)

Cold-adapted yeasts from Antarctica and the Italian Alps—description of three novel species: Mrakia robertii sp. nov., Mrakia blollopis sp. nov. and Mrakiella niccombsii sp. nov. - Skye Robin Thomas-Hall; Benedetta Turchetti; Pietro Buzzini; Eva Branda; Teun Boekhout; Bart Theelen; Kenneth Watson (Extremophiles, 2010)

Production of volatile organic compounds (VOCs) by yeasts isolated from the ascocarps of black (Tuber melanosporum Vitt.) and white (Tuber magnatum Pico) truffles - Pietro Buzzini; Chiara Gasparetti; Benedetta Turchetti; Maria Rita Cramarossa; Ann Vaughan-Martini; Alessandro Martini; Ugo Maria Pagnoni; Luca Forti (Archives of Microbiology, 2005)